Hexameric MnII Dendrimer as MRI Contrast Agent. Issue 44 (15th September 2014) - Zhu, Jiang; Gale, Eric M.; Atanasova, Iliyana; Rietz, Tyson A.; Caravan, Peter
Abstract A MnII chelating dendrimer was prepared as a contrast agent for MRI applications. The dendrimer comprises six tyrosine‐derived [Mn(EDTA)(H2O)]2− moieties coupled to a cyclotriphosphazene core. Variable temperature 17O NMR spectroscopy revealed a single water co‐ligand per MnII that undergoes fast water exchange (kex=(3.0±0.1)×108 s−1 at 37 °C). The 37 °C per MnII relaxivity ranged from 8.2 to 3.8 mM−1 s−1 from 0.47 to 11.7 T, and is sixfold higher on a per molecule basis. From this field dependence a rotational correlation time was estimated as 0.45(±0.02) ns. The imaging and pharmacokinetic properties of the dendrimer were compared to clinically used [Gd(DTPA)(H2O)]2− in mice at 4.7 T. On first pass, the higher per ion relaxivity of the dendrimer resulted in twofold greater blood signal than for [Gd(DTPA)(H2O)]2−. Blood clearance was fast and elimination occurred through both the renal and hepatobiliary routes. This MnII containing dendrimer represents a potential alternative to Gd‐based contrast agents, especially in patients with chronic kidney disease where the use of current Gd‐based agents may be contraindicated.